A Comparison Study of Reactive Power Control Strategies in Wind Farms with SVC and STATCOM - Nazha Cherkaoui; Touria Haidi; Abdelaziz Belfqih; Faissal El Mariami; Jamal Boukherouaa (Institute of Advanced Engineering and Science, 2018)
In the recent years, the integration of the wind farms into the electrical grids has increased rapidly. Especially, the wind power plants made up with doubly fed induction generators due to its many advatanges, such as being able to control its reactive power. Hence, some countries have published grid code requirements related to the reactive power that the wind turbines have to satisfy. This paper presents a coordinated reactive power control strategy in which STATCOM and doubly fed induction generators in wind power plants are used in order to bring back the voltage at the point of common coupling in the allowable range. First, reactive power requirements that the wind farms have to fulfill in some European countries are introduced. Second, the reactive power limitations of 2MW doubly fed induction generator are determined. Then, the static synchronous compensator (STATCOM) and the synchronous var compensator (SVC) FACTS (Flexible AC Transmission Systems) devices are presented. Finaly, various reactive power control strategies are applied to 10 MW wind farm, and the simulation results are analysed and compared.